Exploring perceptions of diabetes distress and its care in Japan: a qualitative study of patients and physicians - Kyoko Akano; Taro Sugihara (BMJ Open)
Objectives This study aimed to identify the obstacles preventing care of diabetes distress from being integrated into diabetes management, as perceived by both patients and healthcare professionals. By conducting interviews with people with type 2 diabetes (PWD) and physicians, this study aimed to gain insight into the current state of care for diabetes distress in diabetes management and propose targeted interventions to improve patients’ overall well-being and treatment outcomes.Design This qualitative study used semistructured interviews with patients and physicians. The interviews followed a guide with open-ended questions to gather detailed, reflective responses about participant experiences, perceptions and attitudes towards the research topic.Setting This study targeted stakeholders in type 2 diabetes care in Japan.Participants Nine PWD and nine physicians participated in the interviews. The patients had been receiving treatment for more than 5 years, and the physicians had at least 1 year of clinical experience in diabetes treatment and had treated a minimum of five PWD per month. The physicians were recruited through snowball sampling.Results This study uncovered four primary themes. Patients and physicians had differing perceptions of diabetes distress, with patients experiencing psychological challenges, such as anxiety over self-management and fluctuating blood glucose levels, while physicians focused on poor adherence and financial constraints. PWD often felt responsible for managing their condition, leading to self-blame and reluctance to seek emotional support from healthcare providers (HCPs). Physicians faced constraints in providing psychosocial support owing to limited resources and insufficient training. HCPs support affected patient motivation and clinic visits, with positive reinforcement and understanding fostering self-management, whereas one-sided guidance had negative effects. Patients frequently used self-tracking data to enhance their self-management and effectively communicate with HCPs. These data provided valuable insights for treatment planning and helped bridge gaps in the monthly laboratory results.Conclusion This study highlights significant discrepancies between patients’ and physicians’ perceptions of diabetes distress. Effective communication and trust building are essential for addressing the psychological needs of patients. The integration of self-tracking data can enhance patient–HCP interactions and support better diabetes management. Addressing these gaps can improve care of diabetes distress in clinical practice, leading to better quality of life and treatment outcomes for PWD.